Evaluasi Tingkat Kualitas Pelayanan Pasien Rawat Jalan Menggunakan Metode Importance Performance Analysis (Studi Kasus RS Wava Husada Malang) - As’ady, BJ. Azmy; Yogiyopranoto, Muhammad; Purwadhi; Widjaja, Yani Restiani (Innovative: Journal Of Social Science Research, 2025)
Quality outpatient services are crucial for patient satisfaction and loyalty. This study aims to assess the performance and determine the priority of service improvement of Wava Husada Hospital Malang outpatient installation. The Importance Performance Analysis method was applied to 27 attributes based on five dimensions of quality, through a Likert scale questionnaire that assesses perception (performance) and expectations (importance). The average performance score of 3.9 and importance of 3.8 resulted in a positive gap of 0.1, indicating that patient satisfaction has been met. Kartesius diagram placed five attributes among them waiting time, staff responsiveness, schedule accuracy, queue compliance, and politeness in quadrant A, requiring immediate improvement, while the other ten attributes were in quadrant B and needed to be maintained. Overall, the hospital was able to provide services beyond expectations, but time discipline and fast response must continue to be improved in order to maintain competitive advantage.